INTERVENÇÃO EDUCATIVA INTERDISCIPLINAR PARA PROMOVER O CONSUMO DE HORTALIÇA ENTRE CRIANÇAS EM AMBIENTE ESCOLAR - Soares, Jaqueline Machado (2020)
The food profile of children follows a worldwide trend towards the expressive consumption of foods with high concentrations of sugar, sodium and fat. In addition, the consumption of fruits and vegetables is usually neglected due to lack of knowledge, low incentive and low acceptance. This has been reflected in high rates of overweight and obesity in childhood. There are many efforts worldwide to reverse this scenario, including government food, nutrition and health programs. The food industry has also been looking to develop healthier products, enriching food products with nutrient-source foods. Thus, interdisciplinary research involving the areas of Nutrition, Food Technology, Food Engineering and Pedagogy can be an alternative to identify the best intervention strategies during childhood. The present study was carried out in three stages, the first consisting of a literature review with the context of the study theme. The second stage aimed to evaluate the effect of adding eggplant flour to cookies on the physical-chemical and nutritional characteristics and to verify the sensory acceptability among school-aged children. In the third stage, an educational action was developed with cooking workshops to enable the inclusion of eggplant in the usual diet of children. In the review study, aspects of the development of school-age children, the determinants associated with the children's food and nutritional profile, alternatives for healthy food consumption, government food and school nutrition programs and food and nutrition education strategies were addressed. In the second stage, the most nutritious and healthy food that presented the least acceptance (eggplant) among schoolchildren in Guarapuava, PR was used as an ingredient in the preparation of a product commonly consumed by children - cookie. Four cookie formulations were prepared: standard, with 0% eggplant flour, and the others added 2.5%, 5% and 7.5% eggplant flour. The samples were evaluated for sensory acceptability, physical-chemical and nutritional composition. In the development of the cooking workshops (step 3), the children actively participated in the preparation of the eggplant cookie. The tasks were related to cleaning, cutting and mixing ingredients and finalizing the recipe. It was found that higher levels of eggplant flour (7.5%) in the cookie reduced acceptability among children (p <0.05). The addition of the flour changed the physico-chemical characteristics of the product. The nutritional profile of the cookie improved with the addition of eggplant flour, since there was an increase in the contents of ash, dietary fiber, ascorbic acid, total phenolic compounds, anthocyanins and in the antioxidant activity and reduction in the carbohydrate and energy content. The development of culinary workshops was a facilitating strategy for children's learning, with promising results for the consumption of a food of low acceptance by school-age children, as well as for the construction of knowledge involving healthy eating habits. It is concluded that the use of eggplant flour in cookies can be considered a viable alternative to improve most of the physical-chemical and nutritional characteristics of the product. In addition, it can increase the possibilities of eggplant consumption, since the use of the culinary workshop as a sensory education tool guarantees a greater willingness of children to try the food later.